Electric Factors in Wound Healing - Farber, Paulo Luiz (Adv Wound Care (New Rochelle), 2021)
Significance: Electric factors such as electric charges, electrodynamic field, skin battery, and interstitial exclusion permeate wound healing physiology and physiopathology from injury to re-epithelialization. The understanding of how electric factors contribute to wound healing and how treatments may interfere with them is fundamental for the development of better strategies for the management of pathological scarring and chronic wounds. Recent Advances: Angiogenesis, cell migration, macrophage activation hemorheology, and microcirculation can interfere and be interfered with electric factors. New treatments with various types of electric currents, laser, light emitting diode, acupuncture, and weak electric fields applied directly on the wound have been developed to improve wound healing. Critical Issues: Despite the basic and clinical development, pathological scars such as keloids and chronic wounds are still a challenge. Future Directions: New treatments can be developed to improve skin wound healing taking into account the influence of electrical charges. Monitoring electrical activity during skin healing and the influence of treatments on hemorheology and microcirculation are examples of how to use knowledge of electrical factors to increase their effectiveness.